Quasi-2D Perovskite Crystalline Layers for Printable Direct Conversion X-Ray Imaging - Tsai, Hsinhan (Advanced materials (Deerfield Beach, Fla.), 2022)
© 2022 The Authors. Advanced Materials published by Wiley-VCH GmbH. This article has been contributed to by US Government employees and their work is in the public domain in the USA.